E-commerce and India's retail and manufacturing sectors - Some lessons for ensuring sustainable development - Nibha Bharti; Sugandha Huria; Ashley Jose; Kanika Pathania (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
The sudden surge in the e-commerce sector has sparked concerns in several economies in the world, particularly in India. The country's traders' associations have complained that the online retail sector (dominated by e-commerce majors) has been growing at the expense of the offline retail sector, primarily the MSMEs. In this context, this study marks one of the initial endeavours to analytically evaluate the impact of the thriving online retail industry on India's organised manufacturing and retail segments. The results indicate that, while online retailing has assumed a significant role in positively impacting the sales of the overall retail and manufacturing sector of the country (on average) during the period 1989-2020, the same effect has not been observed for its MSMEs. The impact on MSMEs has been positive, though not significant - indicating the untapped potential of the MSME sector to take advantage of the growing online commerce. Similar results hold for the retail sector and retail MSMEs when it comes to the impact on their international trade participation due to the growing online retail sector. Finally, the study also underscores the importance of "digitalisation" as a prerequisite for accessing the e-commerce channel, aligning with the societal and environmental objectives outlined in the 2030 Agenda for Sustainable Development. Consequently, the findings advocate setting up a comprehensive e-commerce regulatory framework in India to ensure sustained and inclusive growth for both the e-commerce and MSME sectors.
hdl:20.500.12870/6771
Keywords: F14; F23; L86; D22; 330; E-commerce; India; Retail Sector; Manufacturing Sector; MSMEs; SDG 2030